2016
DOI: 10.1074/jbc.m115.699801
|View full text |Cite|
|
Sign up to set email alerts
|

Structural and Biochemical Insight into the Mechanism of Rv2837c from Mycobacterium tuberculosis as a c-di-NMP Phosphodiesterase

Abstract: The intracellular infections of Mycobacterium tuberculosis, which is the causative agent of tuberculosis, are regulated by many cyclic dinucleotide signaling. Rv2837c from M. tuberculosis is a soluble, stand-alone DHH-DHHA1 domain phosphodiesterase that down-regulates c-di-AMP through catalytic degradation and plays an important role in M. tuberculosis infections. Here, we report the crystal structure of Rv2837c (2.0 Å ), and its complex with hydrolysis intermediate 5-pApA (2.35 Å ). Our structures indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 42 publications
(24 reference statements)
7
66
0
Order By: Relevance
“…1). It has been reported that CnpB can also cleave c-di-GMP (24) and nanoRNA (23). Therefore, we determined whether the regulation of the cas genes by CnpB is mediated by c-di-GMP or nanoRNA.…”
Section: Rna-seq Analysis Revealed That Cnpb Controls Expression Of Tmentioning
confidence: 98%
“…1). It has been reported that CnpB can also cleave c-di-GMP (24) and nanoRNA (23). Therefore, we determined whether the regulation of the cas genes by CnpB is mediated by c-di-GMP or nanoRNA.…”
Section: Rna-seq Analysis Revealed That Cnpb Controls Expression Of Tmentioning
confidence: 98%
“…Although the structural basis for the recognition of cyclic di-AMP by the PDEs remains to be fully defined, the crystal structure of the standalone DHH/DHHA1 protein Rv2837c in complex with the hydro-lytic intermediate 5-pApA suggests that a set of residues from both DHH and DHHA1 domains contribute to the binding of cyclic di-AMP (94). Even assuming that only two families of cyclic di-AMP phosphodiesterases are found in nature, identification of the members of the two families by bioinformatics should still proceed with caution, and experimental validation is necessary.…”
Section: Functional Diversification Of Cyclic Di-amp Phosphodiesterasesmentioning
confidence: 99%
“…2A) and is proximal to the predicted substrate binding site (Fig. 2B) (32). To elucidate how the adaptive mutation may facilitate daptomycin resistance, we determined the phosphodiesterase activity of E. faecalis GdpP I440S toward its potential physiological substrate c-di-AMP.…”
Section: C-di-amp Signaling In Enterococcimentioning
confidence: 99%